A Regional Model of Innovative Eco-system and Its Application to Kazakhstan - Aldabergenov, Karimzhan (2016)
Innovation is a new way of economic diversification. This dissertation provides a critical analysis of the process of creating an innovative eco-system by comparing and contrasting the main actors and features of three different models, namely Silicon Valley, Route 128 and the Finnish model. Through a qualitative methodology based on secondary data, this dissertation tries to find a way to integrate these three models and a complementary one in order to present a unique model. It generalizes innovation as three common features and presents the five most important key elements to develop an eco-system which might become a basis for innovation activities. Lastly, this work tries to apply its unique model to the Kazakhstan context, and shows why and how it is possible to use it.